CRIMINAL LAW ARRANGEMENTS AGAINST JUSTICE COLLABORATORS IN CORRUPTION CRIMES IN INDONESIA - Heru Suhendro; Yasmira Mandasari Saragih (Journal of International Islamic Law, Human Right and Public Policy, 2024)
In various countries, the form of legal protection for Justice Collaborators and Westleblowers is different. Legal protection for Justice Collaborators was first known in Italy, at that time a member of the Italian mafia, Joseph Valachi, testified about the crimes committed by his group, then followed in America and Australia with legal protection. Meanwhile, in Indonesia, regulations regarding the actions of a Justice Collaborator or Westleblower are regulated in joint regulations with law enforcement officials and circulars from the Supreme Court. In giving testimony, Justice Collaborators are generally motivated by reducing their prison term or from their heart they really want to repent. However, in testimony, sometimes a Justice Collaborator is disturbed or obstructed by fellow colleagues who have committed a crime, and this is something that needs to be regulated by every country in the world so that the dismantling of a criminal case can run optimally. In responding to corruption cases, countries in the world have responded with various regulations so that they can have a deterrent effect on perpetrators of these crimes, they have also included regulations regarding Westleblowers and Justice Collaborators in their country's laws. However, in Indonesia the rules regarding witnesses, perpetrators and reporters are only regulated in the 2011 Supreme Court circular and joint regulations with law enforcement officials and the LPSK. It is appropriate that regulations regarding protection for reporting witnesses and cooperating perpetrator witnesses be included in our country's laws, so that the brave mentality of these witnesses can continue.